Providence, Fortune, and the Experience of Combat: English Printed Battlefield Reports, circa 1570-1637 - Randall, David (The sixteenth century journal, 2004)
Printed English-language battlefield news reports between 1570 and 1637 conveyed to English newsreaders a genre-distinctive discourse of war, whose emphasis on the precise means of battlefield providence conveyed a degree of experimental providentialism considerably beyond the norms of England's consensually providential culture. This article examines closely the relationship of the news genre to its usage of providence and fortune, and shows how and why providence emerged as its favored explanatory concept. It also looks at the usual contexts of battlefield providence, and shows how these contributed to the pronounced emphasis on experimental providentialism within these news reports' descriptions of the battlefield. Finally, it highlights the suggestive affinities between these news reports' experimental providentialism and the experimental providentialism of English Puritans, and by so doing considers the possible effects the news reports' peculiar providentialism may have had on the English reading public.